Caracterización de la demanda turística colombiana en función de los destinos turísticos de la región 1 y la provincia de Pichincha de Ecuador - García Moreira, David Reinaldo (2019)
The objective of the present study was the characterization of the Colombian tourist demand based on the perception, typology and satisfaction of the destination of Ecuador especially to the sites located in the north of continental Ecuador. A five-stage methodological process was established based on the study of demand, the supply of tourism products and services, strategic tourism analysis, marketing plan and determination of marketing strategies. In the first stage, an analysis of the current situation is performed according to the study of variables, based on documentary collection; the study of the supply was analyzed through the conformation of the tourist services and their impacts in the study area; Five tourist destinations were evidenced with diverse and integrated tourist products and Quito was ranked as the main tourist destination in the north of Ecuador. For the analysis of the demand two types of survey were developed; depending on the motivations and degree of satisfaction of the Colombian tourist ( Rumichaca ); The statistical research identified three types of segments or profiles of Colombian tourists visiting the northern area of Ecuador. The positioning of the destination Ecuador was established, in comparison with the ten most demanded Latin American countries by Colombian tourists; The motivations for the trip constitute a determining factor to assess the perception of the destination Ecuador (survey applied in the city of Cali). The strategic tourism analysis with the use of the SWOT matrix in a participatory diagnosis with technicians from different disciplines of the Ministry of tourism (MINTUR) on the Zone 1 and the province of Pichincha, it allowed to analyze a total of 182 variables (indicators), 10 strategies were determined, implemented through 24 tourism projects, aimed at improving the positioning and image of the destination.